Japan Through the Lens of the Tokyo Olympics - Holthus, Barbara; Gagné, Isaac; Manzenreiter, Wolfram; Waldenberger, Franz (Taylor & Francis, 2020)
"This book situates the 2020 Tokyo Olympics within the social, economic, and political challenges facing contemporary Japan. Using the 2020 Tokyo Olympics as a lens into the city and the country as a whole, the stellar line up of contributors offers hidden"